SAT0248 A multicenter study assessing the efficacy and safety of repository corticotropin injection in patients with rheumatoid arthritis: preliminary interim data from the open-label treatment period. (12th June 2018) - Fleischmann, R.; Furst, D. E.; Brasington, R.; Connolly-Strong, E.; Liu, J.; Barton, M. E.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disorder associated with chronic inflammation that is commonly treated with disease-modifying anti-rheumatic drugs (DMARD) and corticosteroids. Repository corticotropin injection (RCI) is approved in the United States as adjunctive therapy for short–term administration (during an acute episode or exacerbation) in RA (selected cases may require low dose maintenance therapy). Objectives: This is an interim analysis from a multicenter, 2–part study evaluating the efficacy and appropriate duration of RCI therapy in patients with persistently active RA despite receiving 1–2 DMARDs and corticosteroids. Methods: The study includes a 12-week open-label treatment period followed by a 12-week double–blind randomized maintenance phase for patients who achieve low disease activity (LDA) at Week 12. During the open–label period, all enrolled patients received RCI 80 U subcutaneously (SC) twice per week. The primary endpoint was the proportion of patients that achieved LDA (ie, disease activity score with 28 joint count and erythrocyte sedimentation rate [DAS28-ESR] score <3.2) at Week 12. The secondary endpoints were proportion of patients that maintained LDA from Week 12 to Week 24, time to disease activity flare, safety, and tolerability. Disease activity was also assessed by the proportion of patients that achieved improvements in American College of Rheumatology (ACR)20, ACR50, and ACR70 scores at Week 12. Results: As of December 18, 2017, 45 patients had completed the 12-week open-label treatment period of the study, and 12 patients had discontinued; 77.8% were female, with a mean age of 57 years. Patient baseline characteristics and the results of the primary and select secondary endpoints are presented in table 1, demonstrating that RCI allowed the majority of patients with RA to achieve LDA at Week 12. To date, 21 adverse events (AEs) and 1 serious AE (chest pain) have been reported. The most common AEs were headache (3), urinary tract infection (2), and fall (2). Conclusions: Interim results from this ongoing clinical trial suggest that RCI can potentially be a safe and effective treatment alternative to improve multiple measures of disease activity in patients with persistently active RA despite therapy with DMARDs and corticosteroids. Acknowledgements: Editorial support was provided by MedLogix Communications, LLC, Itasca, IL, under the direction of the authors and was funded by Mallinckrodt ARD, Inc., Bedminster, NJ. Disclosure of Interest: R. Fleischmann: None declared, D. Furst: None declared, R. Brasington: None declared, E. Connolly-Strong Shareholder of: Mallinckrodt, ARD Inc, Employee of: Mallinckrodt, ARD Inc, J. Liu Shareholder of: Mallinckrodt, ARD Inc, Employee of: Mallinckrodt, ARD Inc, M. Barton Shareholder of: Mallinckrodt, ARD Inc, Employee of: Mallinckrodt, ARD Inc